PENINGKATAN KREATIVITAS DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL THINK PAIR SHARE - Simanjuntak, Rusmayanti; Waruwu, Ermina (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This study aims to apply the Think Pair Share model to improve students' creativity and learning outcomes in SD Swasta Santo Petrus Medan. The Classroom Action Research (PTK) involved 28 students from Phase B Class IV of the 2023/2024 academic year. The steps of the research method carried out start from planning, implementation, observation, and reflection. Data collection methods include tests, observation, and documentation. Qualitative descriptive analysis is used, with process and product success criteria. Results showed a significant increase in the application of Think Pair Share and Student Creativity such as Introduction (83% to 92%), Think (83% to 92%), Pair (75% to 92%), Share (75% to 100%), Award (75% to 100%). Likewise, there was an increase in student creativity Producing original ideas (8.75% to 18.83%), Producing original works and actions( 7.77% to 16.70%), Having flexibility of thinking in finding alternative solutions to problems (7.85% to 16.16%). Recommendations encompass strengthening educators' creativity, curriculum evaluation, and enhancing teaching strategies to achieve students' holistic learning outcomes.